Pharmacy staffing and workload in RSGM Unpad using Workload Indicators of Staffing Needs (WISN) method - Faisal Kuswandani; Dwintha Lestari; Felisha F. Balaﬁf (Indonesian Journal of Clinical Pharmacy, 2021)
Introduction : One of the challenges in the health facility is the balance between the number of staff and workloads to achieve quality, effectiveness and efficiency. Developing countries that have limited resources and budgets finds out difficult to achieve it. This study aims to analyze the workload at Pharmacy RSGM Unpad using the Workload Indicators of Staffing Needs (WISN) from the World Health Organization (WHO). Methodology: The study employed descriptive cross-sectional design and the Workload Indicator of Staffing Needs (WISN) methodology. Conducted in May 2020. We utilized observations, discussion and interviews to obtain information from staff; document review from hospital's records in 2019. Results :  Available work time in a year were 97440 minutes. As a result, the staffing needed  the Inpatient-outpatient department in Pharmacy RSGM Unpad were 4 people and in the logistic-purchasing department in Pharmacy RSGM Unpad were 2 people. The WISN ratio was obtained at 1.17 (> 1) which means the workload and number of staff at Pharmacy RSGM Unpad were not appropriate (overstaff). Conclusion : Based on the analysis using the WISN method, the number of staff in the Pharmacy RSGM Unpad is overstaff the existing workload. The Pharmacy RSGM Unpad can redistribute staff and develop pharmaceutical satellites to increase effectiveness and efficiency.